A KAJIAN POTENSI INTERAKSI OBAT PADA PASIEN GERIATRI DENGAN GAGAL JANTUNG DI RSUD Dr. MOEWARDI SURAKARTA TAHUN 2023 - Safira, Della Anggun; Amrullah, Adhi Wardhana; Rahardjoputro, Rolando (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Geriatric patients with heart failure generally receive more than 1 type of drug therapy, called polypharmacy, which typically involves at least four types of treatment: ACEI (Angiotensin Converting Enzyme Inhibitors), diuretics, beta blockers, and digoxin. This causes an increase in the occurrence of drug interactions. This study aims to determine the potential drug interactions that occur in geriatric patients with heart failure who undergo hospitalization at Dr. Moewardi Surakarta Hospital from January to December 2023. This study is a descriptive observational study with a cross-sectional design, and the data were collected retrospectively using a purposive sampling technique based on the medical records of geriatric patients at Dr. Moewardi Surakarta Hospital in 2023. The inclusion criteria were inpatients aged ≥55 years who were diagnosed with heart failure. The exclusion criteria were patients with incomplete or illegible medical record data or who died during treatment. Drug interaction research was conducted based on Drugs.com and Medscape. The results showed that out of the 100 patients, 98 experienced drug interactions. The incidence of drug interactions was 252 minor cases (21.65%), 818 moderate cases (69.50%), and 106 major cases (9.00%). The mechanism of drug interaction was pharmacodynamic in 919 cases (65.50%), pharmacokinetic in 213 cases (30.40%), and unknown in 44 cases (4.10%).